Policy environments and job loss: Lived experience of retrenched Australian automotive workers. (May 2013) - Anaf, Julia; Newman, Lareen; Baum, Frances; Ziersch, Anna; Jolley, Gwyneth
Job loss has negative consequences for health and evidence shows that the agency of workers experiencing job loss is affected by labour market and welfare policy. The policy environment into which workers emerge after losing their jobs strongly influences the way job loss and its aftermath is experienced. This article draws on findings from two waves of in-depth semi-structured interviews with 33 retrenched South Australian automotive workers. It discusses how, within the context of Australian welfare and industrial policy, workers experienced the consequences of mass job losses that occurred at Mitsubishi Motors during 2004 and 2005. Key findings include largely negative experiences associated with negotiating welfare-to-work policy, and a more precarious employment environment further entrenched under industrial relations policy. Job loss is both a personal and a structural story and we use an agency and structure perspective to examine how workers' agency was enabled, but more often constrained, by policy.